2021
DOI: 10.1007/s40520-021-01894-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and coronavirus disease 2019 (COVID-19): rapid evidence review

Abstract: Background The rapid global spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease 2019 (COVID-19), has re-ignited interest in the possible role of vitamin D in modulation of host responses to respiratory pathogens. Indeed, vitamin D supplementation has been proposed as a potential preventative or therapeutic strategy. Recommendations for any intervention, particularly in the context of a potentially fatal pandemic infection, should be st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Definitive randomised controlled trials are lacking and the one well-conducted trial undertaken to date has shown no effect, albeit in a relatively small population [ 9 ]. We do not view the evidence base as conclusive one way or the other—the underlying biology, in terms of 1,25(OH) 2 D, as Dr Grant suggests, and as we documented in our review, would be compatible with an effect of vitamin D on COVID-19 [ 2 ]. Additionally, a large meta-analysis of supplementation for reduction in (non-COVID-19) respiratory infections also supports the possibility of an effect on this outcome [ 10 ].…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Definitive randomised controlled trials are lacking and the one well-conducted trial undertaken to date has shown no effect, albeit in a relatively small population [ 9 ]. We do not view the evidence base as conclusive one way or the other—the underlying biology, in terms of 1,25(OH) 2 D, as Dr Grant suggests, and as we documented in our review, would be compatible with an effect of vitamin D on COVID-19 [ 2 ]. Additionally, a large meta-analysis of supplementation for reduction in (non-COVID-19) respiratory infections also supports the possibility of an effect on this outcome [ 10 ].…”
mentioning
confidence: 89%
“…We read with interest the letter [ 1 ] from William B Grant, director of the Sunlight, Nutrition and Health Research Centre, San Francisco, commenting on our narrative review of the evidence around vitamin D and COVID-19 disease [ 2 ]. Dr Grant suggests that confounding and reverse causality, at least as addressed in studies to date, do not account for associations between vitamin D and COVID-19 disease, where these have been observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High latitude, dark skin type, overweight, inflammatory conditions, are all predisposing factors for severe vitamin D deficiency (serum 25(OH)D below 25 nmol/l) [ 1 ]. The authors of the latest rapid evidence review for vitamin D and Covid-19 [ 2 ] find the evidence not compelling enough to advise population-wide prophylactic vitamin D supplementation to prevent Covid-19 severity. They confirm, however, vitamin D’s role in immune modulatory processes.…”
mentioning
confidence: 99%
“…The recent review by Raisi-Estabragh and colleagues [ 1 ] concluded that evidence to support vitamin D supplementation for the prevention or treatment of COVID-19 is inconclusive. The main reasons given for reaching this conclusion were confounding considerations and reverse causation in observational studies, and limited data from intervention studies.…”
mentioning
confidence: 99%